2016
DOI: 10.18632/oncotarget.10305
|View full text |Cite
|
Sign up to set email alerts
|

A classical PKA inhibitor increases the oncolytic effect of M1 virus via activation of exchange protein directly activated by cAMP 1

Abstract: Oncolytic virotherapy is an emerging and promising treatment modality that uses replicating viruses as selective antitumor agents. Here, we report that a classical protein kinase A (PKA) inhibitor, H89, synergizes with oncolytic virus M1 in various cancer cells through activation of Epac1 (exchange protein directly activated by cAMP 1). H89 substantially increases viral replication in refractory cancer cells, leading to unresolvable Endoplasmic Reticulum stress, and cell apoptosis. Microarray analysis indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…This fact has also prompted us to test whether combining M1 with various chemical compounds enhances the oncolytic effect in refractory tumor cells in which M1 inhibits less than 25% of cell viability (15). For example, we recently reported that the activation of cyclic adenosine monophosphate (cAMP) and exchange protein directly activated by cAMP1 (Epac1) signaling pathways enhances the oncolytic effect of M1 (15,16), which supports our hypothesis.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…This fact has also prompted us to test whether combining M1 with various chemical compounds enhances the oncolytic effect in refractory tumor cells in which M1 inhibits less than 25% of cell viability (15). For example, we recently reported that the activation of cyclic adenosine monophosphate (cAMP) and exchange protein directly activated by cAMP1 (Epac1) signaling pathways enhances the oncolytic effect of M1 (15,16), which supports our hypothesis.…”
supporting
confidence: 79%
“…We have previously shown that cancerselective replication underlies the cancer targeting property of M1 (6,15,16). To understand whether the replication of M1 virus is affected by SMCs, we analyzed the effect of SMCs on the replication of M1 virus.…”
Section: C-iap1 and C-iap2 Play Key Roles In The Enhanced Oncolytic Ementioning
confidence: 99%
“…The effects of cAMP that are not accounted for by the use of PKA inhibitors are not to be disregarded, as they could have specific roles in the cellular response to potentially confounding signals. The choice between PKA and EPAC1 as an effector thus could possibly be determined, not only by the expression pattern of these molecules but also possibly by the spatial and temporal compartmentalization of cAMP, which could have differential effects, as recently documented for b2AR [103][104][105].…”
Section: Effector Pathways-pka and Epac1mentioning
confidence: 96%
“…In general, EPAC and PKA mediated signaling pathways function antagonistically, independently or synergistically in rare occasions to modulate cancer cell proliferation, apoptosis, adhesion, and migration (193,361,473,474,722,1030,1073). Activation of cAMP/EPAC1 signaling pathways has also been reported to sensitize refractory cancer cells to oncolytic virotherapy (605,606).…”
Section: B Role Of Epac In Cancersmentioning
confidence: 99%